How social change leaders practice reflexivity in an integrated way and realise its emancipatory aim - Ongaro, Patrizia (Graduate School of Business (GSB), 2026)
Social change leaders seek to help those marginalised by some of the most pressing social problems of our time. The underlying assumptions informing how ‘help' is understood and given may, however, remain overlooked, producing disempowering rather than empowering outcomes for the ‘helped'. Such assumptions and related relationships and power imbalances can be examined through the practice of reflexivity. My literature review explores the meaning of reflexivity and reflexive leadership. I derive four calls of reflexivity from the literature: to question assumptions, to interrogate power relations, to relate with others and the Other, and to live with heart. The literature review also shows that reflexivity acknowledges the interconnected and embodied nature of experience. Yet while there is evidence of siloed, and mostly discursive, reflexive practice, there is a scarcity of literature on the integrated enactment of reflexivity that is inclusive of embodied as well as dialogical practices. While reflexivity's emancipatory effect is referenced in the literature, the mechanism by which reflexivity might achieve this aim is unclear. The resulting research question that responds to this gap in the literature is: How do social change leaders practise reflexivity in an integrated way, and how does this practice fulfil reflexivity's emancipatory aim? Aligned with positive organisational scholarship, I chose to study leaders within two social change organisations as positive cases in that they demonstrated apparent accomplishments in reflexive leadership, with empowering results for participants. I designed a phenomenological research methodology that gave precedence to experiential, embodied and relational research design elements. This took the form of arts-based methods (including clay work, photography, and drawing) combined with interviewing. I also designed and implemented three original arts-based methods: family mapping, dialogue writing and letter writing. Interpretive phenomenological analysis (IPA) informed the analysis of data, as well as the design of the study. In my findings, I discover that leaders take on a critically reflexive role in identifying and responding to the contextual threats and trauma that the intended participants of their social change interventions encounter. They design and then engage in numerous reflexive practices with participants which are mutually supportive to form an integrated whole. I call this integrated reflexive practice (IRP). The constituent practices are bodying (including inter-bodying); dialoguing; seeing, hearing and caring for; and the fostering of physical and emotional safety. Collectively these develop participant self-reflexivity. I show how these practices are reflexive and interrelated. I further show that IRP empowers participants by interrupting pathways from their contextual threats/trauma to habituated defensive action (characterised by the psychological defence mechanism of splitting), developing instead reciprocity and choice towards integration, which in turn leads towards participant empowerment. The study contributes to the literature on prosocial reflexive leadership by identifying a constellation of interrelated, mutually supportive reflexive practices that form a holistic whole. Trauma is flagged as an important contextual feature, which shapes both the need and opportunity for IRP. I also develop the concept of inter-bodying as a foundational aspect of such reflexive practice, involving the empathic sensitization to the other and to context, through conscious, physical presence. I offer practical implications for leaders, students and educators to develop IRP towards empowerment. These implications become increasingly relevant as leaders manage themselves and others in contexts of greater ambivalence and uncertainty.